Use of Modified Glucose-Insulin-Potassium Mixture in Cardiosurgical Patients - V. N. Poptsov; Ye. V. Morozyuk; B. Yu. Bogomolov (Общая реаниматология)
The investigation was undertaken to study the hemodynamic and metabolic effects of modified (with elevated glucose and insulin levels) glucose-insulin-potassium (GIP) mixture in the correction of acute heart failure in cardiosurgical patients. After infusion of the modified GIP mixture (0.9 g of glucose per kg body weight and 3.75 units of insulin per g glucose), in 15 patients (12 males and 3 females) aged 35 to 72 (54±5) years the increase (p<0.05) in cardiac index and stroke volume index was 21% with simultaneous 20 and 17% decreases in pulmonary wedge pressure and mean pulmonary pressure, respectively (p<0.05). The duration of infusion was 5 hours. A steady-state improvement of cardiac pump function and metabolic parameters could reduce the dosage of cardiotonic drugs 12 hours after administration of the modified GIP mixture. During and after administration of the mixture, the blood levels of glucose and potassium were substantially unchanged. In the study group, all the patients survived. The duration of a resuscitative period was 2.4±0.2 days. With the management protocol used, infusion of the modified GIP mixture was favorable to the steady-state improvement of cardiac pump function without carbohydrate and electrolyte homeostatic impairments.acute heart failure; glucose-insulin-potassium mixture